AI-Based Business Model Innovation: A ChatGPT Integration Approach - Bongard, Florian; Moormann, Jürgen (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
This paper addresses a significant gap in the current literature by exploring the configuration of AI to support the process of business model innovation. Design science research is applied, and a ChatGPT-based prototype is developed to generate business models by recombining industry-independent business model patterns. The aim is therefore to investigate how such an AI assistant can be effectively configured. The study uses case studies from various industries to demonstrate the configured chatbot and evaluate its ability to adapt to different industry contexts and provide customized, innovative business models. The findings were used for refining the prototype, demonstrating its capabilities and evaluating the results. The assessment of the usability and performance of the AI assistant indicates the potential of the prototype and future developments. The study shows that the explorative configuration process can serve as a blueprint for all researchers and practitioners who want to develop innovative business models.